Fabrication of Silicon Nanopillar Sheet for Cell Culture Dish - Ali, Mohammad Yeakub; Mohd Fuad, Nurul Hajar (Department of manufacturing and Materials,Kulliyyah of Engineering, IIUM, 2010)
This paper discusses the fabrication of nanopillars using focused ion beam (FIB) sputtering. A 25 keV Ga+ FIB was used to machine the nanopillars. A reversed bitmap method was used to fabricate nanopillars where it milled the substrate all over except the nanopillar area. The height of the nanopillars ranges from 1 to 5.5 μm with aspect ratio of 1-6. Empirical relationship of taper angle, aspect ratio and height of the nanopillar were established. Taper angle was found to be reduced as the height of the nanopillar increased. The taper angle of nanopillars depends on the acceleration voltage, probe current and dwell time.